A Survey of Hydrological Systems in the Great Virunga Landscape: Water resources assessment and use in and around Mgahinga Gorilla National Park and Echuya Central Forest Reserve, S.W Uganda - Bitariho, Robert; Babaasa, Dennis; Kasangaki, Aventino; Twinamatsiko, Medard; Ayebare, Sam; Mabirizi, Daniel (My University, 2015)
The Greater Virunga Landscape (GVL) is an interconnected chain of eleven protected areas that straddle the borders of Uganda, Rwanda and Democratic Republic of Congo. The landscape is famous for its mountain gorillas (Gorilla beringei beringei) and other endangered and endemic flora and fauna. Human threats in some of the Protected Areas (PAs) in the GVL include uncontrolled exploitation of forest resources as well as fires and the indirect pressures of demand for land. This is exacerbated by the insufficient water supply in communities that border with most of the PAs. Mgahinga Gorilla National Park and Echuya Central Forest Reserve are part of the GVL and were the focus for this study. This report summarizes findings of a hydrological assessment study, conducted during December 2013 up to December 2014 in Mgahinga and Echuya forests. To understand the water use/need and quality used by the local people, this study carried out a socioeconomic survey of households around the two forests. A GIS modeling of floods/soil erosion hazard areas was also carried out to identify the high-risk areas in terms of water quantity and quality; mapping out and inventorying the main water sources in the two forests was also carried out. Furthermore, a hydrological assessment of the water sources was also carried out to understand the physical, chemical and biological compositions of the water regimes (water quality). Last but not least, an MS database of the water quantity and quality was made for the Mgahinga and Echuya landscape to be used for future monitoring purposes of the hydrological systems in the GVL. Socioeconomic survey results show that communities around Mgahinga and Echuya forests were vulnerable to water access and supply (quantity and quality). Areas around Mgahinga have fewer water sources and points than those around Echuya. The few water sources in Mgahinga may be because of the porous nature of the soils and probably exacerbated by climate change effects due to swamp drainages and forest clearances there. It was reported by the local people that there is insufficient water supply from the major water sources in Kisoro district such as Chuho whose water levels have substantively reduced over years. Local communities around Echuya have reported that water quality for domestic use is getting poor due to high levels of soil erosion and seasonal flooding. The major use of water by households was for domestic chores while livestock and irrigation use of water was the least. Average household water use per day was very low and this was calculated at a minimum of 20 litres and a maximum 60 litres for domestic chores use. Most households do not treat or boil water for drinking and other domestic chore use.
Keywords: Hydrological Systems; Water resources assessment; National Park; Uganda